Impact of Islamic Microfinance on Improving the Income and Poverty Reduction on Microenterprises in Province Aceh : Case Study in BaitulQiradh - Asmawati Asmawati; Shofian Ahmad (Sharia and Law Faculty, 2017)
Since 1995 Baitul Qiradhhas been serving low - income people who most lywork asmicro enterprises by providing microfinance in Province Aceh. This study was conducted to assessand analy se the impactofbaitulqiradh’ micro finance services to increase the income andreduce povertyamong therecipients. Primary data were collected from 208 completed questionairres distributed to the clients of 8 BQ in six district/city in Province Aceh, in order to find out their perceptions on their impacts they observed on their socio-economic lives after receiving financing from the institutions in question. The finding show that the average mean income after financing was increased significantly IDR 838.221 (42.92%) than before financing. Socio-economicfactorsthatinfluence the increasecustomer income inthisstudyis thelevelof education, number Offinancing andinvest ment sinen trepreneurial training. The results importantly also found that the financing has help in decrease in poverty among the clients from 39.4% before financing to 12.5% after financing.In order to improve role of baitulqiradh Aceh in area study, this study suggest they have to improve their service not only financial side but also social services, to promote their financing products to community, to making tutorial meeting (monthly) to improve clients understanding on islamic values in a practical way, to be more innovative in desinged their financial product to fulfill the needs of their clients particular and community, and to develop link network to other financial institution (bank and non- bank), NGO dangoverment in implement their activity.